Effects of standardized ileal digestible valine: lysine ratio on nursery pig performance - Clark, A. B.; Tokach, Michael D.; Dritz, Steven S.; Touchette, K. J.; GonAalves, M. A. D.; DeRouchey, Joel M.; Goodband, Robert D.; Woodworth, Jason C. (My University, 2016)
A total of 280 pigs (PIC 327 × 1050; initially 6.53 kg BW) were used in a 28-d trial to evaluate the effects of increasing standardized ileal digestible (SID) Val:Lys ratio on nursery pig growth performance. Pigs were weaned at 21 d of age and 5 pigs allotted to each nursery pen according to BW and gender. A common diet was fed for 5 d when pens were assigned to 1 of 7 dietary treatments in a randomized block design with 8 pens per treatment. Experimental diets were fed from d 0 to 14 followed by a common diet from d 14 to 28. The 7 dietary treatments were 50, 57, 63, 68, 73, 78, and 85% SID Val:Lys. A prior experiment demonstrated a Lys requirement of 1.44 and 1.45% SID Lys for ADG and G:F, respectively, for pigs in this facility. Thus, diets were formulated to 1.24% SID Lys to ensure pigs were below the Lys requirement. As SID Val:Lys increased, ADG, ADFI, and G:F increased (quadratic, P < 0.05). Growth response variables were fitted using linear and nonlinear dose–response models with pen as the experimental unit and initial BW as a covariate with ADG and G:F fitted using heterogeneous and homogenous residual variance, respectively. Models fit were quadratic polynomial (QP), broken-line linear (BLL), and broken-line quadratic with best fit determined according to Bayesian information criterion. For ADG, the best fitting model was BLL and maximum ADG was achieved with a minimum of 62.9% SID Val:Lys (95% CI: [52.2, 73.7%]). For G:F, the best fitting model was QP [0.010294 + 0.017526*(Val:Lys)– 0.000122*(Val:Lys)2] using a 6.53-kg initial BW. This resulted in a maximum G:F at 71.7% SID Val:Lys and 99% of maximum achieved at a 64.4% ratio. In summary, the SID Val:Lys requirement ranged from 62.9 to 71.7% depending on the response model.
Citation: Clark, A. B., Tokach, M. D., Dritz, S. S., Touchette, K. J., GonAalves, M. A. D., DeRouchey, J. M., . . . Woodworth, J. C. (2016). Effects of standardized ileal digestible valine: lysine ratio on nursery pig performance. Journal of Animal Science, 94, 45-45. doi:10.2527/msasas2016-097
Keywords: Amino Acids; Nursery Pigs; Valine; Agriculture